Innovations and Evolution of Metallurgy in Islamic Civilization of the Nusantara Region - Agus Pramono (Nur Science Institute, 2025)
The study explores the transformation of metallurgy in Islamic civilization and its influence on the development of metalworking in Nusantara. Beginning with pioneers such as Khabab bin Al-Arat and Salman Al-Farisi, who introduced alloy technologies such as the creation of Zulfikar's sword, Islamic metallurgy advanced significantly with contributions from Jabir Ibn Hayyan and Reyhan Al-Biruni. This knowledge developed innovative methods, such as sublimation and nanostructure technologies, which found applications in weapons like the Damascus sword. The knowledge was later disseminated to Java by Sheikh Sadzali, who merged Islamic spiritual teachings with local traditions, particularly in keris-making, through figures like Mpu Supo Driyo and his son, Mpu Supo Mandraki. Collaborating with Sheikh Abdul Jalil, they integrated Islamic values into the symbolic designs of keris, blending functionality and spirituality. This research highlights the continuity of Islamic knowledge in advancing global technology while enriching local cultural heritage in Nusantara. Keywords: metallurgy, islamic civilization, keris, archipelago, damascus sword REFERENCES Pramono, A. (2018). The Existence of Metallurgical Science in Islamic Perspective. Journal of Character Education